Community-based ecotourism in Lake Titicaca: a sustainable proposal from the Andean worldview - Cayo-Velásquez, Noemí Emperatriz (2026)
Conventional tourism in Lake Titicaca has generated negative environmental and cultural impacts stemming from motorized transport and extractivist models. Given this context of lacustrine pollution and the loss of local knowledge, there is an urgent need to identify and propose alternatives that harmonize economic activity with principles of ecosystem preservation and identity. The objective was to explore the ecological and cultural viability of sailing tourism as a regenerative alternative grounded in the Andean worldview. Methodologically, the study adopts a qualitative approach with an exploratory and interpretive design, employing documentary review, direct observation conducted in 2024, and comparative analysis of international experiences. The results provide evidence that communities conceptualize the lake as a sacred territory and that the use of ancestral knowledge promotes the adoption of biodegradable materials, such as totora, over invasive technologies. Similarly, climatic conditions and local cultural richness denote the viability of the ecotourism proposal by revitalizing Aymara identity and mitigating the ecologicalfootprint. It is concluded that sailing tourism is an effective tool for environmental education and community management, fostering a reciprocal relationship and integrated sustainability among host communities, visitors, and the lacustrine ecosystem.